2002
DOI: 10.1063/1.1488596
|View full text |Cite
|
Sign up to set email alerts
|

CO on Pt(111) puzzle: A possible solution

Abstract: CO adsorption on the Pt(111) surface is studied using first-principles methods. As found in a recent study [Feibelman et al., J. Phys. Chem. B 105, 4018 (2001)], we find the preferred adsorption site within density functional theory to be the hollow site, whereas experimentally it is found that the top site is preferred. The influence of pseudopotential and exchangecorrelation functional error on the CO binding energy and site preference was carefully investigated. We also compare the site preference energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 45 publications
10
80
1
Order By: Relevance
“…Nevertheless, whereas the tensile surface strain can lower the energy gap between the TB and HH structures, our calculations still predict that the HH overlayer is the most stable. However, it is well known that DFT underestimates the cost of breaking one of the bonds from a triply bonded CO molecule (36). Given that CO in an atop site is close to being doubly bonded and CO in a hollow site is close to being singly bonded, it follows that DFT overestimates the strength of CO adsorption in threefold hollow sites (36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, whereas the tensile surface strain can lower the energy gap between the TB and HH structures, our calculations still predict that the HH overlayer is the most stable. However, it is well known that DFT underestimates the cost of breaking one of the bonds from a triply bonded CO molecule (36). Given that CO in an atop site is close to being doubly bonded and CO in a hollow site is close to being singly bonded, it follows that DFT overestimates the strength of CO adsorption in threefold hollow sites (36).…”
Section: Resultsmentioning
confidence: 99%
“…Given that CO in an atop site is close to being doubly bonded and CO in a hollow site is close to being singly bonded, it follows that DFT overestimates the strength of CO adsorption in threefold hollow sites (36). This explains the discrepancies found between experiment and calculation, where DFT fails to predict the experimentally observed atop-site occupation at low coverage for CO adsorption on both native Pt(111) and Rh(111) (36,37). To reduce or solve completely such site preference discrepancies in DFT, one can use the newly developed van der Waals-density functional (vdW-DF) of nonlocal correction as shown by Lazi c et al (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The article initiated further studies, and in some of them, the top site was found to be lowest in energy: it was argued that the inclusion of relativistic effects should lead to the correct adsorption site [7,8]. Others [9] confirmed the wrong site preference with the top site higher in energy, although a relativistic pseudopotential was used. They argued that the failure was because different bond orders were treated with varying accuracy due to the generalized gradient approximation.…”
Section: Introductionmentioning
confidence: 99%
“…This was first discussed by Feibelman et al [7] where a variety of DFT-GGA methodologies and codes predicted adsorption at the fcc or hcp hollow site to be preferred over the experimentally preferred top site adsorption on the Pt(111) surface at low coverage. Since then this "puzzle" has been addressed [8,9,10,11] and the DFT-GGA inaccuracy traced to the incorrect description of CO electronic structure and bond-breaking.…”
Section: Introductionmentioning
confidence: 99%